A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa - Deschodt, Christian M.; Davis, Adrian L.v.; Scholtz, Clarke H. (Zootaxa, 2016)
Although it has been demonstrated that the tribe Canthonini (Scarabaeidae: Scarabaeinae) is polyphyletic, those canthonine genera occurring in arid south-western Africa apparently form a monophyletic group. In this paper we add one new monotypic genus, Drogo stalsi gen. et. sp. n. to this group, and synonymize another member, Byrrhidium namaquense Scholtz and Howden, 1987 syn. n. with Byrrhidium ovale Harold, 1869. We correct the spelling of two species names that were not in agreement with the gender rule. A phylogenetic analysis based on morphology supports the erection of Drogo gen. n. An updated key to the genera and species of the Byrrhidium group is presented.